The princess in black and the hungry bunny horde ebook - Hale, Shannon (Princess in Black, 2017)
It's a case of monstrous cuteness in the third book of the New York Times best-selling series as the Princess in Black encounters a new challenge: a field overrun by adorable bunnies. Princess Magnolia and her unicorn, Frimplepants, are on their way to have brunch with Princess Sneezewort when Princess Magnolia's glitter-stone ring rings. The monster alarm! After a quick change in the secret cave, Princess Magnolia and Frimplepants are transformed into the Princess in Black and her faithful pony, Blacky. But when they get to the goat pasture, all they can see is a field full of darling little bunnies. Where are the monsters? Are these bunnies as innocent as they appear?